ACUTE TOXICITY OF COPPER, ZINC AND MERCURY ON INTERTIDAL GASTROPODS OF MUMBAI COAST - Jaiswar, A. K.; Kulkarni, B. G.; Thakur, M. K. (Journal of Indian Fisheries Association, 2015)
The acute toxicity test conducted by static bioassay techniques have revealed that among selected heavy metals, copper is more toxic than zinc and mercury to Planaxis sulcatus and Trochus radiatus. The natural availability of heavy metals in the surrounding environment of these organisms is found to be deciding factor for their toxicity. Natural habitat of the animal also contributes to the sensitivity of a particular animal to the heavy metals tested. In addition the tendency of the animal to overcome the adverse conditions in their surrounding also plays a significant role in toxicity of pollutants. Keywords: Intertidal, Nerita oryzarum, Planaxis sulcatus, Trochus radiatus, Copper, Zinc, Mercury